Uji Daya Hambat Ekstrak Bawang Putih terhadap Vibrio sp. dari Tambak Udang Vannamei yang Terkena White Feces Disease (WFD) - Budhi Wahyu Nurindra; Pande Gde Sasmita Julyantoro; Dewa Ayu Angga Pebriani (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
White Feces Disease (WFD), which infects Pacific white shrimp (Litopenaeus vannamei), poses a serious challenge in aquaculture due to its potential to cause mass mortality and substantial economic losses. One of the main causes of this disease is bacterial infection from the genus Vibrio. The use of natural substances, such as garlic (Allium sativum) extract, is considered a more environmentally friendly and sustainable alternative for disease control. This study aimed to examine the effect and determine the optimal concentration of garlic extract in inhibiting the growth of Vibrio sp. isolated from WFD-infected L. vannamei ponds, cultured on TCBS media. The study was conducted in vitro using the disc diffusion method with four extract concentrations (25%, 50%, 75%, and 100%) against two bacterial isolates, designated as isolate A and isolate B. The results showed that garlic extract was able to inhibit the growth of Vibrio sp., with the largest inhibition zone observed in isolate A at 75% concentration (14.8 mm) and in isolate B at 100% concentration (19.3 mm). These findings indicate the potential of garlic as a natural antibacterial agent to inhibit pathogenic bacteria and support the sustainability of shrimp aquaculture.